The change in Singlish : investigating the effects of a changing language ecology on the Singlish lexicon through Singapore-produced media - Chew, Jorene Jo Ee (Nanyang Technological University, 2020)
Singlish is well-known as a colloquial variety of English unique to Singapore heavily influenced by the variety of languages that make up our linguistic ecology. Accordingly, much attention has been paid to this variety that some consider ‘broken’. However, while many have researched its status and/or grammatical and phonological aspects, rare are the studies done on its varied lexicon or the language change that might have affected it. Tan (2017) theorises that Singlish’s form and lexicon are formed of and governed by the languages within Singapore’s linguistic ecology and their degree of prominence. Based on this model, 2 Singaporean movies of similar genres and produced nearly 2 decades apart were chosen to identify how a changing linguistic ecology affects the Singlish lexicon. Singlish lexical items were extracted from the movies and glossed before being analysed by origin language and the movies in which they occurred. The findings of the study indicate that the language shifts undergone by society did have some impact on Singlish’s lexical items. However, overall, the variety proved to be relatively stable and seemed to possess some form of a ‘core’ vocabulary formed of its more commonly used lexical items. This leads to the conclusion that Singlish, remains somewhat influenced by its parent varieties. However, it has slowly begun outgrowing the influence of its ‘parents’ and may eventually come into itself as an independent linguistic variety.